A set of software components for the simulation of plant airborne diseases. (October 2015) - Bregaglio, Simone; Donatelli, Marcello
Abstract: Models to evaluate the impact of plant diseases on crop production under current and future climatic conditions are increasingly requested by different stakeholders. This paper presents four software components – InoculumPressure, DiseaseProgress, ImpactsOnPlants, AgromanagementDisease – which implement models to simulate the dynamics of generic polycyclic fungal epidemics and interactions with crop physiological processes. The software architecture adopted allows extending the components with alternate approaches to reproduce specific pathosystems or compare predictive capabilities. As proofs of concept, (i) the components are coupled with two crop simulators to reproduce wheat brown rust and rice blast epidemics and their impacts on leaf area and yield formation; (ii) spatially distributed sensitivity analyses are performed for rice in China and wheat in Europe to investigate model behaviour; (iii) a preliminary evaluation against observations of rice blast severity is performed in Northern Italy. The components are explicitly targeted to the modelling of crop–pathogen interactions to perform scenario analysis. Highlights: We present four software components to simulate plant–pathogens interactions. Each component is devoted to the modelling of different aspects of plant diseases. The components are framework independent and can be extended by third parties. We couple the components to crop simulators and perform model sensitivity analysis. The main target of the components is their application in scenario analysis.